Graphene oxide–mediated electrochemistry of glucose oxidase on glassy carbon electrodes. (14th July 2015) - Castrignanò, Silvia; Valetti, Francesca; Gilardi, Gianfranco; Sadeghi, Sheila J.
Abstract: Glucose oxidase (GOD) was immobilized on glassy carbon electrodes in the presence of graphene oxide (GO) as a model system for the interaction between GO and biological molecules. Lyotropic properties of didodecyldimethylammonium bromide (DDAB) were used to stabilize the enzymatic layer on the electrode surface resulting in a markedly improved electrochemical response of the immobilized GOD. Transmission electron microscopy images of the GO with DDAB confirmed the distribution of the GO in a two‐dimensional manner as a foil‐like material. Although it is known that glassy carbon surfaces are not ideal for hydrogen peroxide detection, successful chronoamperometric titrations of the GOD in the presence of GO with β‐d ‐glucose were performed on glassy carbon electrodes, whereas no current response was detected upon β‐d ‐glucose addition in the absence of GO. The GOD–DDAB–GO system displayed a high turnover efficiency and substrate affinity as a glucose biosensor. The simplicity and ease of the electrode preparation procedure of this GO/DDAB system make it a good candidate for immobilizing other biomolecules for fabrication of amperometric biosensors.